2008
DOI: 10.1111/j.1468-0335.2008.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Booms and Busts: Consumption, House Prices and Expectations

Abstract: Over much of the past 25 years, the cycles of house price and consumption growth have been closely synchronised. Three main hypotheses for this co-movement have been proposed in the literature. First, that an increase in house prices raises households' wealth, particularly for those in a position to trade down the housing ladder, which increases their desired level of expenditure. Second, that house price growth increases the collateral available to homeowners, reducing credit constraints and thereby facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
257
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(278 citation statements)
references
References 16 publications
7
257
5
Order By: Relevance
“…But there is no evidence here that the active savings being accumulated by renters in younger cohorts have been 'compensating' for their lack of homeownership: trends in amounts being saved across cohorts look no better for renters than for homeowners. 54 A failure of lower housing wealth to depress the expenditure (and so increase the saving) of those still renting in younger cohorts would correspond to a finding in work by Attanasio et al (2009). Those authors concluded that the observed correlation between house prices and consumer spending was the result of common factors driving both, rather than individuals' expenditure responding to changes in housing wealth.…”
Section: Cohort Comparisons Of Property Wealthmentioning
confidence: 76%
“…But there is no evidence here that the active savings being accumulated by renters in younger cohorts have been 'compensating' for their lack of homeownership: trends in amounts being saved across cohorts look no better for renters than for homeowners. 54 A failure of lower housing wealth to depress the expenditure (and so increase the saving) of those still renting in younger cohorts would correspond to a finding in work by Attanasio et al (2009). Those authors concluded that the observed correlation between house prices and consumer spending was the result of common factors driving both, rather than individuals' expenditure responding to changes in housing wealth.…”
Section: Cohort Comparisons Of Property Wealthmentioning
confidence: 76%
“…That is, the high covariances lengthen the effective horizon of households that are likely movers, and so the wealth effect from a change in house prices will often be largely offset by changes in housing costs in both current and expected future housing markets. 18 These results can help explain the small marginal propensities to consume out of housing wealth estimated by Attanasio et al (2009) …”
mentioning
confidence: 97%
“…One explanation for the estimated housing wealth effect is the common-factor hypothesis (Attanasio et al [2009]). Under this hypothesis, shocks to a common unobservable factor, such as expected future income, simultaneously affect the demand for housing services (which, with an inelastic supply, in turn affects house prices) and non-housing consumption.…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not make any statements about the economic nature of the common factor that drives the housing wealth effects in the actual data. For instance, in reality, this common factor could be shocks to expected income (e.g., Attanasio et al [2009] and Calomiris et al [2009]), general confidence in the economy (e.g., Case et al [2005Case et al [ , 2013), or changes in the non-housing wealth. Our econometric results do not rely on the economic nature of the common factor; instead, they rely on two assumptions.…”
mentioning
confidence: 99%
See 1 more Smart Citation